LO03: Validation of The Ottawa Troponin Pathway. (May 2019) - Lam, B.; Li, J.; Mukarram, M.; Nemnom, M.; Booth, R.; Thiruganasambandamoorthy, V.
Abstract : Introduction : Our team developed "The Ottawa Troponin Pathway" (OTP) for Non-ST Elevation Myocardial Infarction (NSTEMI) diagnosis using serial conventional troponin (cTnI) 3 hours apart to aid in safe and early disposition of ED patients. The primary objective of this study is to validate the diagnostic accuracy of the OTP in the cohort of patients with cTnI values above the 99th percentile ( > 45ng/L).Methods : This study is a health records review conducted at the Civic and General Campuses of The Ottawa Hospital from August 2017 to December 2017. Adults (≥18 years) who presented to the ED with symptoms of ACS, and who had serial cTnI (at least two values 3 hours ±15 minutes apart) performed for diagnosis of NSTEMI and at least one cTnI value > 45ng/L were included. Patients with cardiac arrest, STEMI, unstable angina or those with TnI values ≤45ng/L were excluded. The outcomes were death due to unknown cause or NSTEMI adjudicated by two blinded investigators within 30 days. Data collected include baseline characteristics, ED management, length of stay, cTnI values and times of measurement, disposition, and outcome. We used descriptive statistics and test diagnostic characteristics to analyze our data.Results : We screened 53, 077 patients, of whom 635 patients were included in the study (mean age 71.6 years; 57.6% males; 59.7% hospitalized; median ED length of stay 4.7 hours.). 107 patients (16.9%; 95%CI 14.1%-20.0%) were diagnosed with NSTEMI within 30 days. Among patients with TNI values above the 99th percentile, the OTP did not miss any patients diagnosed with NSTEMI. The sensitivity and the specificity of the OTP were 100% (95%CI 96.6%-100%) and 32.2% (95%CI 28.2%-36.4%) respectively.Conclusion : Our results show that the OTP is diagnostically accurate in ruling out NSTEMI among patients with cTNI values above the 99th percentile with symptoms concerning for ACS. Using the OTP will allow for early referral to consulting services for management, safe and early discharge home, and improve ED crowding.